1984
DOI: 10.1530/jrf.0.0720329
|View full text |Cite
|
Sign up to set email alerts
|

Effects of oestradiol benzoate treatment on the reproductive performance and endocrine status of sows after lactations of 10 or 35 days

Abstract: Forty-two Landrace X Large White sows were used in 3 studies of oestradiol benzoate treatment 24 h (E1) or 48 h (E2) after piglet removal, following lactations of 10 (S) or 35 (L) days, or were untreated controls (C). For Exp. 1, oestradiol benzoate doses were 4, 16 and 64 micrograms/kg body weight; since highest mean LH peaks followed use of the 16 micrograms/kg dose, this treatment was used in later studies. Treatments for Exp. 2 were S-E1 and L-E1 (N = 3). Pregnancy rates were 1/3 and 2/3, respectively, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1987
1987
2004
2004

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Finally, in lactating sows, the hormones and neurotransmitters associated with suckling could block the discharge of GnRH and that of LH in response to high levels of oestrogens. In weaned sows, the duration of lactation influences the responsiveness to OB; the amplitude of the oestrogen-induced LH surge is higher after 35 than after 21 or 10 d of lactation (Edwards and Foxcroft, 1983b;Kirkwood et al, 1984b).…”
Section: Ovarian Activitymentioning
confidence: 99%
“…Finally, in lactating sows, the hormones and neurotransmitters associated with suckling could block the discharge of GnRH and that of LH in response to high levels of oestrogens. In weaned sows, the duration of lactation influences the responsiveness to OB; the amplitude of the oestrogen-induced LH surge is higher after 35 than after 21 or 10 d of lactation (Edwards and Foxcroft, 1983b;Kirkwood et al, 1984b).…”
Section: Ovarian Activitymentioning
confidence: 99%
“…It has recently been suggested that the mechanism(s) involved in reducing embryo survival following previous short lactation lengths or lowlevel lactation feed intake have a common cause involving either a reduction in plasma gonadotrophin levels (Aherne and Kirkwood 1985) or a reduced ovarian response to gonadotrophic stimulation (Kirkwood et al 1984b(Kirkwood et al , 1987. This hypothesis is indirectly supported by evidence from recent studies with cattle demonstrating an improvement in pregnancy rates of 8-13% following the administration of gonadotrophin -releasing hormone (GnRH) at insemination or during the 6 h preceding it (Schels and (Table 3).…”
mentioning
confidence: 99%
“…Additionally, a decrease in LH plasma level in the treated gilts could be eventually the consequence of the inhibitory effect of the proinflammatory cytokines released from an inflamed uterus on the hypothalamicpituitary unit, as was suggested earlier [33]. The reduction of PRL secretion observed in E. coli-treated animals can be caused by the decreased oestrogen secretion [34,35] and/ or cytokine effect [9,36].…”
Section: Discussionmentioning
confidence: 99%